Oxidized LDL and NO synthesis—Biomarkers of endothelial dysfunction and ageing. (November 2015) - Gradinaru, Daniela; Borsa, Claudia; Ionescu, Cristina; Prada, Gabriel Ioan
Graphical abstract: Highlights: OxLDL and NO play antagonistic roles in endothelial dysfunction. OxLDL and NO are relevant biomarkers in vascular ageing and ageing-related diseases. Metabolic status and oxidative stress are major determinants of oxLDL and NO activity. The ratio of oxLDL to NO x – a new marker of endothelial dysfunction. Abstract: Oxidized LDL (oxLDL) and nitric oxide (NO) exert contradictory actions within the vascular endothelium microenvironment influencing key events in atherogenesis. OxLDL and NO are so far regarded as representative parameters of oxidative stress and endothelial dysfunction, new targets in prevention, diagnosis and therapy of cardiovascular diseases, and also as candidate biomarkers in evaluating the human biological age. The aim of this review is to explore recent literature on molecular mechanisms and pathophysiological relationships between LDL oxidation, NO synthesis and vascular endothelium function/dysfunction in ageing, focusing on the following aspects: (1) the impact of metabolic status on both LDL oxidation and NO synthesis in relation with oxidative stress, (2) the use of oxidized LDL and NO activity as biomarkers in human studies reporting on cardiovascular outcomes, and (3) evidences supporting the importance of oxidized LDL and NO activity as relevant biomarkers in vascular ageing and age-related diseases.